Uses of underground water resources in the Hydrographic Circumscription Surrounding the Furnas Reservoir - Deus, Franciny Oliveira; Latuf, Marcelo Oliveira (Sociedade & Natureza, 2022)
In the recent decades, there has been an intensification of the use of water resources to meet the various demands of the society and, in this bias, groundwater has been used with a greater frequency and volume, due to the lesser influence of meteorological variations on its availability. On the other hand, the collection of groundwater is more expensive when compared to the surface water, since it depends on geological surveys for its use. In the surroundings of the Furnas reservoir, located in the south of the state of Minas Gerais, Brazil, there are demands for the use of groundwater resources such as irrigation, industry and, human consumption, among others. In this sense, the study aims to understand the spatio-temporal dynamics of underground grants granted in the Hydrographic Circumscription of the Surroundings of the Furnas reservoir in the period from 2001 to 2020, in order to subsidize decision support actions to the management bodies in the various administrative spheres. Therefore, data from underground grants from the Minas Gerais Institute for Water Management were used, where they were processed through electronic spreadsheets and descriptive statistics techniques. On the other hand, the Geographic Information System was used to obtain continuous density surfaces of deferred grants, as well as consumed flows. Results show that 624 underground grants were granted in the study area between 2001 and 2020 and that, from 2013 onwards, there was a significant increase in the amount granted, and the user segments that had the greatest demands represented the supply of public/human consumption and irrigation/agribusiness consumption respectively. In this context, it is essential that the managing body, as well as the Hydrographic Basin Committee around the Furnas Reservoir, carries out the planning and the management in relation to the groundwater resources, in order to avoid future scenarios of conflicts due to the multiple uses of the underground water.